Hymn of Humanity in Askar Mahkam’s Poetry - Nasiba, Djumaniyazova; Gulshoda, Baxtiyorova (Research Parks Publishers, 2023)
In this article, human feelings, views of the creator about the real person, the role of the poet's work in the education of the youth of the future generation and the formation of high human qualities in them are studied in the poetry of Askar Mahkam.